“He Didn’t Follow the Usual Path of a Narrow Specialist…”: A Contribution to the Biography of Vasyl Maslov (1885–1959) - Maryna Budzar (Київські історичні студії)
Documentary collections of Ukrainian scholars remain an important source for researching the biographies of both individual figures and entire museum curator, and ethnographer Vasyl Maslov enables a more detailed analysis of one of the least studied periods in the scholar’s life: his time in Kyiv during the Nazi occupation of the city. For this publication, the scholar’s autobiography, dated November 1941, and a review of his scientific work authored by Natalia Polonska-Vasylenko, dated October 1942, were selected. The methods employed to integrate these sources into scholarly discourse include comparative analysis, attribution, and source chronology. This approach allows for an examination of the documents within their historical context. Maslov’s autobiography was analyzed through comparison with similar texts written under different conditions and at other times. Polonska-Vasylenko’s essay on Maslov’s body of work was studied as a conceptual text. The author presented the scholar’s contributions across various fields of humanities as a result of interdisciplinary research. Both sources aid in understanding Vasyl Maslov’s work as a scholar whose life bridged the experience of imperial-era academic science with the practices of new Ukrainian humanities amidst the Sovietization of Ukraine. The publication of these documents is complemented by visual sources, including photographs taken during the period discussed in the autobiography and the review.